Egg weight estimation and the effect of age and plumage colors on some egg quality traits in Japanese quails (Coturnix coturnix japonica) - Arslan, Emre; Güler, Serdar; Çetin, Orhan; Sarı, M. Mücahit; Yonar, Harun (Emirates Journal of Food and Agriculture, 2023)
The aim of this study was to investigate the effect of different age and plumage color on the egg quality traits and cholesterol levels, in addition to which traits can be used for egg weight prediction in Japanese quails. The eggs obtained from 23-week-old original plumage colored Japanese and Jumbo quails, and 39-week-old Jumbo quails; 40, 40, and 20 eggs were used respectively as the research material. The eggs obtained from 23-week-old original plumage colored Japanese and Jumbo quails, and 39-week-old Jumbo quails; 40, 40, and 20 eggs were used respectively as the research material. In terms of plumage color difference, when Japanese quails were compared to Jumbo quails; yolk weight, yolk height, yolk diameter were higher, and likewise the cholesterol level was lower (P<0.01). The lowest cholesterol content was found in eggs from 23-week-old Japanese quail (P<0.01). Egg width, shape index, yolk height, and shell weight in group 1; albumen weight, yolk diameter, and egg volume in group 2; egg volume and egg length data in group 3 have determined the best fit for estimation of the egg weight. As a result, the plumage color is a factor that affected the egg quality traits and cholesterol level in quails. Furthermore, some egg quality traits may be used to establish the equations for estimation of the egg weight. Keywords: Age; Egg quality traits; Egg weight estimation; Plumage color; Quail